Elite athletes' condition before, during, and after the COVID-19 lockdown: Insights from AthletesPort data - Shimizu, J.; Shimizu, K. (Journal of High Performance Sport, 2025)
This study investigated changes in Japanese elite athletes' condition before, during, and after the COVID-19 lockdown period, utilizing data obtained from the web-based application "AthletesPort" operated by Japan High Performance Sport Center. A total of 78 elite athletes were included in the analysis, and comparisons were made across three distinct time periods: prelockdown (T0), during lockdown (T1), and post-lockdown (T2). The findings revealed that, during T1, both bedtimes and wake-up times were delayed, leading to an increase in mean sleep duration and a significant reduction in the proportion of athletes obtaining less than seven hours of sleep. Furthermore, subjective sleep quality and perceived fatigue scores improved during T1 compared to T0 and T2. The incidence of dehydration and upper respiratory tract inflammation was also lowest during the lockdown period. These results suggest that the restrictions on daily activities and the closure of training facilities during the lockdown period afforded athletes greater flexibility in their daily routines and provided an opportunity to compensate for previously insufficient sleep. The lockdown term thus served as a catalyst for elite athletes in Japan to re-evaluate lifestyle habits that impact their health and performance, underscoring the critical importance of adequate sleep.